WASTE MANAGEMENT BY THE DEPARTEMENT OF ENVIRONMENT AND SANITATION OF AMBON CITY - Sariyowan, Stephanie; Ohoiwutun, Stanislaus K.; Patty, Julia Theresia (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This research is a qualitative descriptive study aimed at understanding how the Department of Environment and Sanitation of Ambon City manages waste. The research was conducted at the Department of Environment and Sanitation of Ambon City by collecting primary data through interviews with key informants directly involved in waste management activities in Ambon City. The results of the study revealed that waste management in Ambon City is still carried out conventionally through a series of activities, including the collection, transportation, and disposal of waste. The study also identified seven major challenges faced by the Department of Environment and Sanitation of Ambon City. These challenges include population growth, which continuously produces waste, limited infrastructure, low public awareness about the importance of waste management, issues with border waste between Ambon City and three sub-districts in Central Maluku Regency, and marine waste with 141 potential sources of waste entering the sea, particularly in Ambon Bay. Additionally, the enforcement of waste regulations and management of levies also pose significant challenges. In addressing these various challenges, the Department of Environment and Sanitation of Ambon City collaborates with the private sector through partnership programs.